Implementasi Active Learning dan Dampaknya pada Partisipasi Belajar Siswa Madrasah Ibtidaiyah di Probolinggo: Kajian Studi Kasus - Misbahul Arifin; Rizqiyani, Ramzatul Widad (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
The study aimed to deeply analyze and examine the implementation of Active Learning by teachers and its impact on student learning participation at Madrasah Ibtidaiyah (MI) Nurul Mun’im. The primary focus was to identify the effectiveness of active pedagogy practices in enhancing student initiative, interaction, and confidence in expressing opinions in the classroom. This qualitative case study was conducted at MI Nurul Mun’im, Probolinggo, utilizing data collected through participatory observation, in-depth interviews, and RPP (lesson plan) document analysis; subjects were selected via purposive sampling. The results demonstrated that the implementation of Active Learning through cooperative models significantly increased student learning participation, with some initiative indicators rising by up to 191%. The most crucial finding was the teachers' success in contextualizing Active Learning with Islamic adab (etiquette) values and initial extrinsic motivation, effectively reducing the fear of failure and establishing a supportive learning environment. The implication of this research is a theoretical contribution to enriching pedagogical models in Islamic educational institutions, where active strategies must be integrated with religious ethics. It is recommended that these findings serve as a foundation for developing teacher training focused on contextual Active Learning for madrasah institutions.